CHARACTERIZATION OF PSEUDOMONAS FLUORESCENS IN DIFFERENT MEDIA AND ITS ANTAGONISTIC EFFECT ON PHYTOPATHOGENIC FUNGI - DEWANGAN, PRASHANT KUMAR; BHUMIKA KOMA; SANGHMITRA BAGHEL; , NIRANJAN KHARE; H. K. SINGH (The Bioscan, 2014)
The present investigation was carried out to screen different media for growth and colony formation of test bacterium Pseudomonas fluorescens and to check its antagonistic activity on fungal plant pathogens by in vitro dual culture techniques. Out of the seven different media tested, King’s ‘B’ media was best with an OD value of 2.50 and 6 X 108 cfu among the different media evaluated. As far as growth was concerned it was fast in King’s ‘B’ medium, fair in Sim agar medium and slow in remaining media tested. In dual culture method, P.fluorescens on co-inoculation with fungal pathogens decreased their growth rate. Maximum inhibition was observed in Sclerotium rolfsii (63.15%) followed by Fusarium oxysporum (61.85%) Rhizoctonia bataticola (55.56%) and R.solani (53.15 %). study.